2016
DOI: 10.5688/ajpe808133
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and Predictors of Cheating in Pharmacy School

Abstract: Objective. To assess the prevalence, methods, and motivations for didactic cheating among pharmacy students and to determine predictive factors for cheating in pharmacy colleges and schools. Methods. A 45-item cross-sectional survey was conducted at all four doctor of pharmacy programs in Northern California. For data analysis, t test, Fisher exact test, and logistic regression were used. Results. Overall, 11.8% of students admitted to cheating in pharmacy school. Primary motivations for cheating included fear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 23 publications
3
29
0
1
Order By: Relevance
“…Coexistence of depression and anxiety can be highly disabling and might result in severe detrimental consequences to the physical, mental and social wellbeing of the affected populations [33,34]. Depression and anxiety might have severe adverse consequences on the academic performance of medical students, their reported quality of life, contribute to substance abuse, decrease empathy, and academic dishonesty [1,35,36]. Previous studies have also shown that poor mental health was a predictor of later psychological distress among practicing physicians [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Coexistence of depression and anxiety can be highly disabling and might result in severe detrimental consequences to the physical, mental and social wellbeing of the affected populations [33,34]. Depression and anxiety might have severe adverse consequences on the academic performance of medical students, their reported quality of life, contribute to substance abuse, decrease empathy, and academic dishonesty [1,35,36]. Previous studies have also shown that poor mental health was a predictor of later psychological distress among practicing physicians [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological distress among students may adversely influence their academic performance and quality of life [ 17 ] and may contribute to alcohol and substance abuse, decreased empathy, and academic dishonesty [ 18 ]. In light of the risks and consequences of psychological morbidity on students and the remarkable growth in university student numbers in Sub-Saharan Africa within the last 30 years [ 19 ], there is a need to understand the prevalence and antecedents of common mental disorders among university students.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors implicated in psychological morbidity among students include academic pressure, demanding workloads. (Elani et al, 2014), worry about own health (Borst et al, 2016), financial concerns, Borst et al, (2016, exposure to patients' suffering in the case of medical students, bertman et al 2016;Bovero et'al., 2014), and student abuse and mistreatment (cook et al 2014; Nguyen 2016).…”
Section: Background To the Studymentioning
confidence: 99%
“…Psychological distress among students may adversely influence their academic performance and quality of life and may contribute to alcohol and substance abuse decreased empathy, and academic dishonesty (Nguyen et al,2016;Mullan et al 2011). In light of the risks and consequences of psychological morbidity on students and the remarkable growth in university student numbers in Sub-Saharan Africa within the last 30 years (Mullan et al 2011).…”
Section: Background To the Studymentioning
confidence: 99%